2002
DOI: 10.1007/s00264-001-0319-z
|View full text |Cite
|
Sign up to set email alerts
|

Piriformis muscle syndrome in 19 patients treated by tenotomy - A 1- to 16-year follow-up study

Abstract: We treated 19 patients with piriformis muscle syndrome. All patients complained of pain in the buttocks and the posterior thigh. Clinically the buttock was tender and passive stretching increased the pain. In ten patients skin sensation was reduced and three had a limp. All patients were treated with tenotomy. At follow-up after an average of 8 (1-16) years, eight patients had pain relief. Two-thirds of the patients evaluated their clinical state as being better.Résumé Nous avons traité 19 malades avec un synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The largest cohorts were published by Fishman et al . [ 18 ], Indrekvam and Sudmann [ 19 ] and Benson and Schutzer [ 17 ]. The results from these three studies, respectively, ranged from 68.8% achieving >50% relief, two thirds improved and 100% excellent or good results.…”
Section: Discussionmentioning
confidence: 99%
“…The largest cohorts were published by Fishman et al . [ 18 ], Indrekvam and Sudmann [ 19 ] and Benson and Schutzer [ 17 ]. The results from these three studies, respectively, ranged from 68.8% achieving >50% relief, two thirds improved and 100% excellent or good results.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate exposure of the proximal portion of the sciatic nerve is guaranteed with the transgluteal approach. Even though this has been accomplished for compressive lesions using much smaller skin incisions elsewhere,[ 3 6 18 22 ] in traumatic injuries, as in our series, wider exposure is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The reports in the literature are varied; most are case reports and small series with variable results. The largest cohorts were published by Fishman et al., 8 Indrekvam and Sudmann, 12 and Benson and Schutzer. 13 The results from these 3 studies showed an improvement achieving more than 50% symptom relief.…”
Section: Discussionmentioning
confidence: 99%